Identification of EMP1 as a critical gene for cisplatin resistance in ovarian cancer by using integrated bioinformatics analysis. (27th January 2023) - Zeng, Qingsong; Yi, Cunjian; Lu, Jinzhi; Wang, Xiaowen; Chen, Keming; Hong, Li
Abstract: Background: Cisplatin resistance is among the main reasons for the poor prognosis of ovarian cancer (OC) patients. Until now, effective biomarkers for predicting cisplatin resistance in OC and specific drugs for reversing this resistance are lacking. This study identified the critical gene associated with cisplatin resistance in OC and provided a potential target for overcoming this resistance. Methods: Differentially expressed genes between cisplatin‐resistant and ‐sensitive OCs were identified by screening public datasets. Survival analysis was conducted to screen prognosis‐related DEGs. CIBERSORT, ESTIMATE, and immune checkpoint genes were used to assess the association between EMP1 expression and tumor microenvironment features. CTRP and GDSC databases were employed to analyze the correlation between EMP1 expression and cisplatin resistance. Furthermore, immunohistochemistry, qPCR, Western blotting, siRNA interference, and the CCK8 assay were performed to verify the role of EMP1 in cisplatin resistance in vitro. Finally, xenograft mouse models were generated to further confirm the role of EMP1 in cisplatin resistance in vivo. Results: EMP1 was identified as a critical gene associated with cisplatin resistance in OC. According to bioinformatics analyses, increased EMP1 expression was linked to higher stromal/ESTIMATE scores as well as greater ICG expression levels. The in vitro experiments showed that EMP1 was highly expressed in cisplatin‐resistant OC tissues and cells, and silencing this EMP1 expression enhanced OC cell sensitivity to cisplatin. Finally, in vivo experiments confirmed that EMP1 promotes tumor growth and cisplatin resistance. Conclusions: EMP1 can act as a predictive biomarker for cisplatin resistance in OC and as a potential therapeutic target. Abstract : In this study, EMP1 was identified as a key gene for cisplatin resistance in ovarian cancer by bioinformatics, and it was verified in vitro and in vivo.